IMPORTANCE AND PROCESS OF STRATEGIC PLANNING IN COMMERCIAL BANKS - Dragosavac, Vladana V (International Journal of Economic Practice and Policy, 2013)
Financial market has faced many changes in recent years. Business environment in which financial institutions operate is characterized with growing competition due to the reduction of purchasing power of many individuals and companies, as a result of the economic crisis. Consequently, banks, as the most numerous financial institutions, have to introduce changes in their business and to take steps towards innovating their products, so that they create a chance for survival. In such circumstances, it is very important to monitor continuously what happens in the environment and in accordance with that, to take steps and plan future business. This is why a strategic planning in banks can be illustrated as one of the most important factors for their long-term survival.